Answer:
372
Step-by-step explanation:
We are given that the dimensions of the box are,
Length = 15 cm, Width = 20 cm and Height = 9 cm.
We know that the box represents a cuboid.
Since, surface area of a cuboid = L×W + 2×L×H + 2×W×H
Thus, the surface area of the box = 15×20 + 2×15×9 + 2×20×9
i.e. Surface area = 300 + 270 + 360
i.e. Surface area = 930.
Thus, the surface area of the box is 930 cm² i.e. 9300 mm².
Further, the sides of the tiles are 5 mm and the tile represents a square.
So, the surface area of the tile = 5 × 5 = 25 mm².
This gives us that,
Number of tiles required to cover the box = = 372.
Hence, Dmitri requires 372 tiles to cover the box.
The slope and y-intercept of a linear equation can be identified directly from the graph. In this case, the y-intercept is 9 and the slope is 3, making the equation of the line y = 3x + 9.
In Mathematics, we often work with linear equations, which can be represented graphically as a straight line. The slope and y-intercept are two key aspects of this equation and can be obtained directly from the graph. Specifically for problem 6, your line graph has x on the horizontal axis and y on the vertical axis, and intersects the y-axis at the point (0,9). This tells us that the y-intercept (represented by b in the equation) is 9. Furthermore, the slope (represented by m in the equation) is the rise over run, or change in y over change in x. In this case, for every 1 unit increase in x, y increases by 3 units, so the slope is 3. Therefore, the standard form of the line equation would be "y = 3x + 9."
#SPJ2
Answer:
0
Step-by-step explanation:
Using the algebraic expansion
x³ + y³ = (x + y)³ - 3xy(x + y)
Given
x³ + y³ - 12xy + 64
= (x + y)³ - 3xy(x + y) - 12xy + 64
Substitute x + y = - 4 into the expression
= (- 4)³ - 3xy(- 4) - 12xy + 64
= - 64 + 12xy - 12xy + 64
= 0
Answer:
Given : JKLM is a rectangle.
Prove: JL ≅ MK
Since, by the definition of rectangle all angles of rectangles are right angle.
Thus, In rectangle JKLM,
∠ JML and ∠KLM are right angles.
⇒ ∠ JML ≅ ∠KLM
Since, JM ≅ KL (Opposite sides of rectangles are congruent)
ML ≅ ML ( Reflexive )
Thus, By SAS congruence postulate,
Δ JML ≅ Δ KLM
⇒ JL ≅ MK ( because corresponding parts of congruent triangles are congruent)
Hence proved.